An Approach to Retroperitoneoscopic Urological Surgery - Naser, Md Fazal; Hossain, Md Abul; Azam, Md Shafiqul; Alam, Abm Muksudul; Barua, Uttam Kumar; Saha, KP; karmakar, K; Hossain, Md Shohrab (Bangladesh Journal of Urology, 2020)
Objectives: To determine the safety and efficacy of retroperitoneoscopic surgery for renal, ureteral and adrenal diseases. Methods: Since October 2013, 62 patients (22 to 65 years old) have undergone retroperitoneoscopic renal, ureteral and adrenal surgery. Patients were included according to the inclusion criteria depending on the specifying disease and operation. Patient were appropriately evaluated and counseled before operation. The retroperitoneal space was created by handmade balloon dissection. Results: Average kidney size was 85 mm (range 50 to 1720) in simple nephrectomy cases, and average renal tumor size was 64 mm (range 48 to 73). Simple nephrectomy in 10, radical nephrectomyin 09, nephrouretectomy in 8, adrenalectomy in 1,decortication of renal cyst in 11, pyeloplasty in 06, transposition of retrocaval ureter in 06 and ureterolithotomy in 11 cases. Operating time varies from 35 min to 221 min, depending upon the procedure.Hospital stay varies from 2 to 7 days in different cases. Conversion from the laparoscopic procedure to open surgery was required in 3 cases. Peritoneal rent occurred in only 2 patients. Conclusions. The laparoscopic retroperitoneal approach is safe and effective for different types of renal, ureteral and adrenal surgery. Perioperative morbidity and hospital stay are reduced. Bangladesh Journal of Urology, Vol. 19, No. 1, Jan 2016 p.3-12